A importância do IPV6 e uma proposta de abordagem para migração - Pacheco, Calvin (2014)
There will be imminent migration to IPv6, due to depletion of IPv4, and there is interest of companies to generate deployment strategies for the new protocol, to avoid impacts business and also because there are more IPv6 services that provide better quality for the network. The main motivations for migration are, provide better security and performance, provide communications services between most elaborated network assets and mobile devices, enabling greater diversity of integration with network equipment. The study also review what can happen if the implementation is postponed, in order to conclude that the companies may suffer damage by preventing the migration. With the purpose of supporting companies in implementing the new protocol, the paper proposes the implementation of a road map.